Science and Sensation in Romantic Poetry - Jackson, Noel (Cambridge University Press, 2013)
This is a book about the literary uses of sensation in the period of British Romanticism. Its subject is a language that emerges in this period for describing forms of sense experience unique to the poet and to the encounter with poetry. Working from a contemporary understanding of aesthetics as a science of aisthesis or sensuous experience, Romantic poets give shape to a literary practice defined in a close relationship to the contemporary sciences of physiology and the science of mind, and develop an aestheticized vocabulary for articulating the social and political ends to which such scientific knowledge was considered crucial